2006
DOI: 10.1073/pnas.0511138103
|View full text |Cite
|
Sign up to set email alerts
|

Homotypic fusion of early endosomes: SNAREs do not determine fusion specificity

Abstract: Membrane fusion in the secretory pathway is mediated by soluble N-ethylmaleimide-sensitive factor attachment receptor (SNARE) proteins. Different fusion steps are thought to be effected by independent sets of SNAREs, but it is unclear whether specificity is determined by an intrinsic specificity of SNARE pairing or by upstream factors. Using a newly developed microscopy-based assay, we have investigated the SNARE specificity of homotypic early endosomal fusion. We show that early endosomes contain multiple set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
175
1
14

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 132 publications
(194 citation statements)
references
References 57 publications
4
175
1
14
Order By: Relevance
“…In contrast, the other conclusion provides the quite divergent concept that SNARE pairing is rather promiscuous and, thereby, largely incapable of regulating fusion specificity. Indeed, in vitro experiments with SNAREs in mammals showed that the endosomal and exocytic SNAREs readily form noncognate and mixed SNARE complexes (43,44) and cause promiscuous RPL fusion by non-physiological SNARE pairing (24). Despite the fact that we used the same approaches with the purified SNAREs and the RPL lipid mixing assay, our conclusions do not fully agree with either of these previous concepts.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…In contrast, the other conclusion provides the quite divergent concept that SNARE pairing is rather promiscuous and, thereby, largely incapable of regulating fusion specificity. Indeed, in vitro experiments with SNAREs in mammals showed that the endosomal and exocytic SNAREs readily form noncognate and mixed SNARE complexes (43,44) and cause promiscuous RPL fusion by non-physiological SNARE pairing (24). Despite the fact that we used the same approaches with the purified SNAREs and the RPL lipid mixing assay, our conclusions do not fully agree with either of these previous concepts.…”
Section: Discussioncontrasting
confidence: 54%
“…Despite the fact that we used the same approaches with the purified SNAREs and the RPL lipid mixing assay, our conclusions do not fully agree with either of these previous concepts. This might be due to the differences in experimental details, including lipid compositions, lipid to protein ratios, and salt concentrations (22,24). Nevertheless, our findings establish that Q-SNAREs are the key components to mediate fusion specificity through the specific assembly of appropriate Qabc-SNARE complexes, whereas R-SNAREs have little contribution.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…The expression constructs for the neuronal SNAREs were the full-length syntaxin-1A (amino acid residues 1-288), its SNARE motif including the transmembrane region (183-288), a cysteine-free variant of SNAP-25A (1-206) and synaptobrevin-2 (full-length protein, 1-116; soluble portion, 1-96; C-terminal fragment of the soluble portion, 49-96) 30,39,45,46 . The expression constructs for endobrevin were the full-length protein (1-100) and its soluble portion (1-74) 46,47 . Full-length syntaxin-4 (1-298) 48 and a variant of SNAP-23 in which cysteine residues were replaced with serines were similarly cloned into the pET28a vector using the NdeI and XhoI restriction sites.…”
Section: Methodsmentioning
confidence: 99%
“…One of the reasons for this gap in our knowledge is that, in contrast to fusion (3,4), it has been difficult to reconstitute sorting from endosomes in vitro. Compared to live cell approaches, in vitro assays allow direct biochemical access to the docking and fusion machineries (for instance, proteins can be depleted or perturbed using cell-impermeant inhibitors such as antibodies).…”
mentioning
confidence: 99%